Cauchy Problem for Dissipative Hölder Solutions to the Incompressible Euler Equations - Daneri, Sara (Communications in Mathematical Physics, 2014)
We consider solutions to the Cauchy problem for the incompressible Euler equations on the 3-dimensional torus which are continuous or Hölder continuous for any exponent θ 1/16. Using the techniques introduced in De Lellis and Székelyhidi (Inventiones Mathematicae 9:377-407, 2013; Dissipative Euler flows and Onsager's conjecture, 2012), we prove the existence of infinitely many (Hölder) continuous initial vector fields starting from which there exist infinitely many (Hölder) continuous solutions with preassigned total kinetic energy. © 2014 Springer-Verlag Berlin Heidelberg.